A Comparison of Antibacterial Effects of Catharanthus roseus and Camellia sinensis (Black Tea) and Their Synergistic Effect along with Antibiotic against Multiple Antibiotic Resistant Strains of Staphylococcus aureus. Issue 2 (3rd April 2021) - Shil, Aparna; Mukherjee, Sushmit; Bishayi, Biswadev; Sikdar (Nee) Bhakta, Mausumi
ABSTRACT: Community associated strains of Staphylococcus aureus were isolated and treated with extracts of Catharanthus roseus and Camellia sinensis (black tea) to examine their antibacterial potential, either alone or in combination with an antibiotic, ampicillin. Results of MIC values (Minimum Inhibitory Concentration), growth inhibitory patterns, SEM images of the clinical and standard strains in the presence of their ethanolic extracts indicated that C. roseus root had greater antibacterial potential than black tea. The FIC (Fractional Inhibitory Concentration) values suggested that the combination of C. roseus root extract and ampicillin had a greater antibacterial activity due to a synergistic effect, than that of the combination of black tea and ampicillin, which exerted an additive effect.